Vanini e l’origine dell’uomo: ambiguità, malizia e dissimulazione nel Dialogo XXXVII del De admirandis - Mario Carparelli (Lexicon Philosophicum, 2024)
At the end of the eighteenth century, Julius Caesar Vanini was considered a precursor of Lamarck and Darwin for his transformative view of biology, which is expressed in particular in Dialogo XXXVII of De admirandis (Paris 1616), where, through a game of simulation and dissimulation based on ambiguity and mischief, he presents radical theses on the origin of man, in stark contrast to creationism and fixism.